Patient delay in the diagnosis and treatment of tuberculosis in China: findings of case detection projects - Lin, Y. (Public Health Action, 2015)
Objective: 1) To assess patient delay among new smear-positive pulmonary tuberculosis (PTB) patients in accessing health services in seven FIDELIS (Fund for Innovative DOTS Expansion through Local Initiatives to Stop TB) projects from 2003 to 2008 in China; 2) to compare treatment delay by province; and 3) to assess factors associated with delay. Method: Records of new smear-positive PTB patients were reviewed. Data sources were the consultation book, laboratory register, patient record, treatment card and the PWLAHS (people with limited access to health services) evaluation form. Data were collected using a standard questionnaire, cross-checked by staff from the sites and by the International Union Against Tuberculosis and Lung Disease (The Union) and analysed by The Union. Results: Of the 75 401 new smear-positive PTB patients included in the study, 63–89% were PWLAHS. The average gross domestic product of the project sites and at national level were respectively US$557 and US$998. The median patient delay was 93 days (range 68–128). Delays were longer among females, older patients, rural residents and PWLAHS. Delayed access to health services was significantly associated with a greater number of symptoms. Conclusion: Patient delay in accessing health care in China was lengthy; TB care and control needs to be improved.